Optic Nerve Atrophy in Syndromic Craniosynostosis. Issue 2 (8th June 2022) - Fearon, Jeffrey A.; Barrientos, Stephan; Ditthakasem, Kanlaya; Herbert, Morley
Abstract : Background: Numerous children born with syndromic craniosynostosis will develop visual impairments. Based on the hypothesis that elevations in intracranial pressure might have greater impacts on vision than development, this review sought to ascertain the prevalence of optic nerve atrophy in syndromic craniosynostosis and to look for potential predictive factors. Methods: The authors conducted a retrospective chart review of all children with syndromic craniosynostosis treated at a single center. Results: Of 442 patients with syndromic craniosynostosis, complete ophthalmologic records were available for 253. Although no instances of optic nerve atrophy were noted among those with Saethre-Chotzen or Muenke syndromes, an overall 14.7 percent prevalence was noted among those with Apert (7.8 percent), Crouzon (27.9 percent), and Pfeiffer syndromes (23.1 percent), with initial diagnoses occurring at a mean age of 10 years. The presence of a Chiari malformation was found to significantly correlate with the subsequent diagnosis of optic nerve atrophy (OR, 3.544; p = 0.002); however, the timing of the first cranial vault procedure, presence of a ventriculoperitoneal shunt, degree of brachycephaly, number of vault expansions, and diagnosis of sleep apnea, did not show significant associations. Conclusions: A substantial percentage of children with Apert, Crouzon, and Pfeiffer syndromes were found to develop optic nerve atrophy, with a prevalence likely to trend higher with longer follow-up. Chiari malformations were the only significant potential predictor for optic nerve atrophy. With the goal of preventing visual losses, more frequent monitoring for raised intracranial pressure with ophthalmologic evaluations and magnetic resonance imaging measurements of optic nerve sheath diameters should be considered. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.